Nationwide incidence of clinically diagnosed retinal vein occlusion in Korea, 2008 through 2011: preponderance of women and the impact of aging - Park, Sang Jun; Choi, Nam-Kyong; Park, Kyu Hyung; Woo, Se Joon (Ophthalmology (Rochester, Minn.), 2014)
This study aimed at defining the incidence and demographics of clinically diagnosed retinal vein occlusion (RVO) in Korea. Nationwide population-based retrospective study using data entered into the Korean national health claims database from 2007 through 2011. Data of the entire population of Korea (n = 47,990,761, based on the 2010 census) were analyzed. The Korean national health claims database was analyzed to identify patients with RVO. Incident cases included individuals with no RVO claims in 2007, but with RVO claims in the years 2008 through 2011. The incidence rate of RVO was estimated for the entire Korean population. The person-time incidence rates of clinically diagnosed RVO in Korea, including the age- and gender-specific incidence rates, were estimated. A total of 92 730 RVO cases (56.4% in women) were identified. The incidence rate of clinically diagnosed RVO during the study period was 48.31 per 100,000 person-years (95% confidence interval [CI], 48.00-48.62). The incidence rate among men and women was 42.40 (95% CI, 41.99-42.81) and 54.14 (95% CI, 53.67-54.60) per 100,000 person-years, respectively (P < 0.001). The highest incidence of 214.92 per 100,000 person-years (95% CI, 211.29-218.56) was observed in the age group of 70 to 74 years (186.62 [95% CI, 181.46-191.78] and 236.25 [95% CI, 231.21-241.29] per 100,000 person-years for men and women aged 70 to 74 years, respectively). The incidence rate of RVO increased as the age of the population increased-more than doubling approximately every 10 years from the second to the seventh decade of life. Retinal vein occlusion occurred more often in men 30 to 54 years of age and in men older than 85 years, but was more common in women 55 to 84 years of age. This study reports the population-based RVO incidence in Korea. The RVO incidence increased exponentially as the age of the population increased, and the RVO incidence in women was 1.28 times higher than that in men.